THE IMPACT OF THE DIMENSIONS OF SOCIAL RESPONSIBILITY ACCOUNTING IN IMPROVING THE PERFORMANCE OF INDUSTRIAL COMPANIES - Hayder Abbas AL-attar (Scholar Express Journals, 2022)
The research aims at measuring the impact of employee development activities on companies’ performance in the short term, identifying the type of relationship between environmental protection activities and companies’ financial performance, and indicating the extent to which companies’ interaction with society reflects on companies’ financial performance. This study was conducted in one of the most important industrial companies affiliated to the Iraqi Ministry of Industry and Minerals, the General Company for Southern Cement, and the study aimed to measure the impact of the areas of social responsibility (employee development, environmental protection, public contributions, and product quality) on the company's financial performance in the short term. The research found that all social responsibility activities lead to improving the company's performance in the short term, and that activities related to employee development are the most influential social responsibility activities on the company's financial performance, followed by the public contributions activity, then the environmental protection activity, and the last product quality activity. The study recommended that the company should pay attention to activities related to the development of workers by providing housing and transportation for them and increasing the number of training courses, as attention to the development and protection of workers improves the performance of the company
Keywords: Social Responsibility; Accounting; Financial; Companies